Buying votes and international organizations: the dirty work-hypothesis - Dreher, Axel; Lang, Valentin; Rosendorff, B. Peter; Vreeland, James Raymond (CESifo working papers, 2018)
We show how major shareholders can exploit their power over international organizations to hide their foreign-policy interventions from domestic audiences. We argue that major powers exert influence bilaterally when domestic audiences view the intervention favorably. When domestic audiences are more skeptical of a target country, favors are granted via international organizations. We test this theory empirically by examining how the United States uses bilateral aid and IMF loans to buy other countries’ votes in the United Nations Security Council (UNSC). Introducing new data on voting behavior in the UNSC over the 1960-2015 period, our results show that states allied with the US receive more bilateral aid when voting in line with the United States in the UNSC, while concurring votes of states less allied with the US are rewarded with loans from the IMF. Temporary UNSC members that vote against the United States do not receive such perks.